2014
DOI: 10.3835/plantgenome2013.11.0039
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Association Mapping and Genomic Selection to Explore PI 88788 Derived Soybean Cyst Nematode Resistance

Abstract: The potential of association mapping (AM) and genomic selection (GS) has not yet been explored for investigating resistance to soybean cyst nematode (SCN), the most destructive pest affecting soybean. We genotyped 282 representative accessions from the University of Minnesota soybean breeding program using a genome-wide panel of 1536 single nucleotide polymorphism (SNP) markers and evaluated plant responses to SCN HG type 0. After adjusting for population structure, AM detected significant signals at two loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
82
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 67 publications
12
82
0
2
Order By: Relevance
“…Locus no. 7 (Gm18-5112839) was not only within the previously reported interval (Winter et al 2007) but also 4 Mb away form an SNP marker (BARC-019001-03050) tagging a previously described locus associated with resistance to SCN HG type 0 (Bao et al 2014). Apart from these overlaps, our GWAS identified 3 novel QTL, including QTL on Chr.…”
Section: Analysis Of Phenotypic Variationmentioning
confidence: 58%
See 1 more Smart Citation
“…Locus no. 7 (Gm18-5112839) was not only within the previously reported interval (Winter et al 2007) but also 4 Mb away form an SNP marker (BARC-019001-03050) tagging a previously described locus associated with resistance to SCN HG type 0 (Bao et al 2014). Apart from these overlaps, our GWAS identified 3 novel QTL, including QTL on Chr.…”
Section: Analysis Of Phenotypic Variationmentioning
confidence: 58%
“…Recent genomewide association study (GWAS) on 282 accessions of soybean breeding lines have detected significant signals at two loci corresponding to rhg1 and FGAM1, plus a third locus located at the end (55.9 Mb) of Chr. 18 underlying resistance to SCN HG type 0 (Bao et al 2014). By using a data set of 55,159 SNPs across 440 diverse soybean landraces and elite cultivars, Han et al (2015) also identified 19 association loci significantly related to the resistance for two SCN HG types.…”
Section: Introductionmentioning
confidence: 97%
“…The potential and limits of genome-wide predictions have been examined for several major crops, such as barley [33], wheat [15, 34–36], maize [37–42], rice [43], sunflower [44], forage plants [45], sugar beet [46, 47], and soybean [48, 49]. The results underlined the potential of genome-wide prediction as a powerful tool to accelerate selection gain in plant breeding.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of predictive modeling with SNP data could also reduce the time needed to stack multiple resistance QTLs into elite cultivars and to select for these QTLs in breeding programs (Bao et al, 2014;Shi et al, 2015). High-throughput genotyping platforms could identify new alleles and genes that can be stacked using MAS to create cultivars with broad-based resistance to SCN.…”
Section: Discussionmentioning
confidence: 99%